2020
DOI: 10.1073/pnas.1915611117
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory and transcriptional landscape associated with carbon utilization in a filamentous fungus

Abstract: Filamentous fungi, such asNeurospora crassa, are very efficient in deconstructing plant biomass by the secretion of an arsenal of plant cell wall-degrading enzymes, by remodeling metabolism to accommodate production of secreted enzymes, and by enabling transport and intracellular utilization of plant biomass components. Although a number of enzymes and transcriptional regulators involved in plant biomass utilization have been identified, how filamentous fungi sense and integrate nutritional information encoded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 77 publications
(93 reference statements)
5
80
0
Order By: Relevance
“…In contrast, non-constitutively expressed genes showed much lower correlations (Figure 1C ). For Neurospora , we analyzed mRNA-seq (FPKM > 1) results from 71 samples that were grown under different nutrient conditions ( 42 ) ( Supplementary Table S2 ). Constitutive genes were defined as those up- or down-regulated by >2-fold in fewer than seven samples.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, non-constitutively expressed genes showed much lower correlations (Figure 1C ). For Neurospora , we analyzed mRNA-seq (FPKM > 1) results from 71 samples that were grown under different nutrient conditions ( 42 ) ( Supplementary Table S2 ). Constitutive genes were defined as those up- or down-regulated by >2-fold in fewer than seven samples.…”
Section: Resultsmentioning
confidence: 99%
“…However, this regulation is strongly carbon source dependent and predominantly occurs at the early stage of fungal growth on lignocellulose. The further comparison of CreA regulon between A. niger and A. nidulans during their growth on crude plant biomass, and the previously identified cellulose-related CreA/CRE1 regulons in Trichoderma reesei ( Antonieto et al, 2014 ), Penicillium oxalicum ( Li et al, 2015 ), and Neurospora crassa ( Sun and Glass, 2011 , Wu et al, 2020 ) showed that a common set of genes were regulated by CreA across different species. In addition, the analysis of binding sites of different TFs in promoter sequences of CreA-regulated genes revealed potential co-regulation between CreA and other important lignocellulose and starch degradation related TFs, such as XlnR ( de Vries et al, 2002a , van Peij et al, 1998 ), AraR ( Battaglia et al, 2014 , Ishikawa et al, 2018 ), RhaR ( Kowalczyk et al, 2017 ), GaaR ( Alazi et al, 2016 , Martens-Uzunova and Schaap, 2008 ) and AmyR ( Tani et al, 2001 ) associated with cellulose, hemicellulose, pectin and starch degradation.…”
Section: Introductionmentioning
confidence: 80%
“…The transcript levels of the homologue of cdt1 and cdt2 genes, Th_75576 and Th_130330 respectively, in T. harzianum LZ117 were also similar to that in K223452, so did the transcript of cltb homologous gene (Th_101977). Cre-1-mediated CCR in N. crassa acts through sugar transporter, transcription factor, sugar catabolism, and PCWDE genes to regulate plant cell wall degradation (Wu et al, 2020). In our results, down-regulation of cre1 did not correlate with enhanced expressions of the master sugar transporters such as cdt1, cdt2, which demonstrate that regulatory mechanism underlying Cre1-mediated CCR might be varied between different fungal species.…”
Section: Changed Genes That Encode Regulators and Major Transportersmentioning
confidence: 51%